Distance Learners’ Experiences of Silence Online: A Phenomenological Inquiry - Duran, Leslie (International Review of Research in Open and Distributed Learning, 2020)
Although learner silence in face-to-face classrooms has been the topic of considerable research interest, relatively little investigation has been done into learners’ experience of silence in distance education. Guided by a phenomenology of practice approach, this study explores the lived experiences of online silence, using interview data gathered from 12 graduate students who were engaged in cohort-based distance learning. Iterative rounds of a whole-part-whole interpretive process were used to identify key themes that emerged regarding the participants’ lived experiences. The findings highlight that silence is a complex, multifaceted phenomenon that was both enacted and received by the participants. Speaking out online was done carefully, sometimes with partial voice and sometimes in fuller voice, sometimes as an obligation and other times with a sense of spontaneity and connection. The six themes that emerged were as follows: (a) learners enact purposeful silence; (b) learners absorb silence from others; (c) learners perceive, and use, silence as demarcation; (d) learners experience silence within voice; (e) learners use deliberate, complex strategies while engaging in online discourse; and (f) learners hear each other in a trusted community. These six themes give new understandings to the experience of online silence. They reflect the multifaceted and nuanced aspects of the phenomenon and have implications for distance education instructors, learners, and curriculum developers.